RI 7165 Miniature Bilevel Alarm For Oxygen-Deficient Atmospheres - Robert A. Bradburn (The National Institute for Occupational Safety and Health (NIOSH), 1968)
The Bureau of Mines has developed a miniature, portable two-level oxygen-deficiency alarm and produced three prototype models. Each operates from a 4.2-v dc power source, and the highest current drain of any model is 80 ma. An electrochemical cell, which produces an electrical output in proportion to the partial pressure of oxygen to which it is exposed, is used as an oxygen detector. The output of the cell is applied to an electronic circuit that detects two different levels of oxygen percentage below that of normal air, and produces distinct audible signals at these levels. The hazard alarm mode is activated when the oxygen percentage first drops below normal and produces a 500-cps "beep" tone with an intermittency of 1 cps. The danger mode produces a continuous 500-cps audible signal when the oxygen percentage drops still lower.